Diseño de control PID para un mecanismo con movimiento espacial ajustado al IoT (2020)
Throughout the history of humanity, the main objective of technological advances has been to facilitate tasks or processes for human beings, some automatisms are even capable of replacing human labor by one hundred percent, as well as the same It works through collaboration between human capacities with the facilities offered by intelligent machines. One of the most used technologies in all types of assisted, semi-assisted or automatic processes is the PID controller, due to its robustness, efficiency and precision, this combined with other components such as actuators and instrumentation devices, form intelligent mechanisms that now range from hand in hand with the internet of things and wireless communication, thus achieving total control over the machines from every point of view. In this project, a prototype-level design is carried out that complies with what has been described, where together with the automated process by a PID controller, the position in two axes of an object is controlled, in the same way applications are suggested for the prototype together with a bibliographic review accompanied by a proposal for the integration of the prototype designed in the concept of Industry 5.0, in this way you will find a book divided into 5 chapters, the first one refers to the bibliographic review and the conceptualization of the future processes to be used, the second describes the process of designing the PID controller, the third relates the design of an Android application with the communication protocol that the project will involve in the world of IoT. In the fourth chapter, the general implementation of the prototype is described, explaining the components and how the previously mentioned processes were joined, and finally in chapter 5 there are the conclusions and recommendations for future projects.